Está en la página 1de 2

# Autor: JOSE LUIS RODRIGUEZ JAVIER Correo: capitancentella_a@yahoo co! !

"

## #OR\$ULAS %ARA DERIVACI&'

n d x = ( n m) x[ n( m+1) ] m dx x

d c =0 dx d c =0 dx d x =1 dx d cx = c dx d du cu = c dx dx d x +c = x dx

n d x = n x n 1 dx c c

n d ln x = 1 n m ln x n m m +1 dx x x

d 1 du u= dx 2 u dx
d n du u = nu n1 dx dx d du cu n = cnu n1 dx dx d ( uv ) = u dv + v du dx dx dx d ( u v ) = du dv dx dx dx d ( u + v ) = du + dv dx dx dx

1 d u x x du = u dx v v dx 2 x

d log a dx

u=

1 du 2u ln a dx

## d dw dv du d du uvw = uv + uw + vw sen( u ) = cos ( u ) dx dx dx dx dx dx d du dv dw u +v w = + dx dx dx dx d du cos ( u ) = sen( u ) dx dx

d u 1 1 du u dv d tan( u ) = sec 2 ( u ) du = dx dx v 2 v u dx v dx dx

d du d 1 1 du cot ( u ) = csc 2 ( u ) ln x + u = 1 + dx dx x + u 2 u dx dx

d dx

x=

1 2 x

d u 1 1 n u = n n dx x x 2 u x

## d du sec ( u) = sec ( u) tan( u) dx dx

d du u= dx dx

d c c du = dx u u 2 dx d c c = 2 dx x 2 x 3
d c c du = dx u 2 u 3 dx

## d c + u 1 du 1 d csc ( u ) = csc ( u ) cot ( u) du ln = dx dx x 2(c u + u ) dx xdx d x 1 1 x du = dx u u dx u x

d u 1 du u dv = 2v u dx 2 dx dx v v
d 1 du arcsen( u ) = 2 dx 1 u dx d 1 du arccos ( u ) = 2 dx 1 u dx

d x 1 = dx c c

d n x = nx n 1 dx
d cx n = cnx n1 dx
n d x = x n 1 dx n

d u x = dx

du u d x 1 du + = 1 x ln( c ) u u dx 2 x dx c c dx

## d 1 du arctan( u ) = dx 1 + u 2 dx d 1 du arc cot ( u ) = dx 1 + u 2 dx

d 1 du arc sec ( u ) = dx u u 2 1 dx

d u 1 du u = dx x x dx x

d c m n dx x

cn = x m

( m+ n) m

d x e = ex dx d u du e = eu dx dx

d x 1 x du d (u v ) = u v du = 1 dx 2 v dx u u u dx dx
d u 1 du nu d u n u n n du m dv = = m m dx x n x 2 dx x dx v v u dx v dx
n d m x dx
n m = n x m m

d 1 du arc csc ( u ) = 2 dx u u 1 dx

d u 1 du = dx c c dx

d c c 1 du n d sen n ( u ) = n cos ( u ) sen( n1) ( u ) du ln( u ) = ln( u ) dx dx x n dx x n u dx x d u dv du u ln( v ) = + ln( v ) dx v dx dx d du sen n ( u ) = n cot ( u ) sen n ( u ) dx dx

d c cn = dx x n x n+1

d dv du cuv = cu + cv dx dx dx

## Autor: JOSE LUIS RODRIGUEZ JAVIER Correo: capitancentella_a@yahoo co! !"

d x 1 = dx c 2c x

d m n nm u ( n m) du d u = dx m dx dx

c m n u

du m m u n+m dx

cn

## d du cos n ( u ) = nsen( u) cos ( n 1) ( u) dx dx d du cos ( u ) = n tan( u ) cos n ( u ) dx dx d du tan n ( u) = n sec 2 ( u ) tan( n 1) ( u) dx dx

d 1 du ln( u ) = dx u dx d n ln x n = dx x

1 du d m n n du d arcvers ( u ) = u = 2 mm u ( m n ) dxdx dx 2v v dx

( )

d u 1 du u dv d u du = u ln ( x ) = + ln ( x ) 3 dx v v dx 2 v dx dx x dx

## d d 1 dv 1 du d u 1 1 du n u d tan n ( u) = n tan n ( u ) csc ( u ) sec ( u ) du x ln ( x ) = 1 + ln x ln( uv ) = + = dx dx v dx u dx dx dx x cx n cx n 2 u dx dx d x ln ( c ) = ln c dx

d u 1 du u dv = dx v v dx v 2 dx

u d c v dx a

## cu du dv d tan n ( u ) = n csc 2 ( u ) tan ( n +1) ( u ) du = ln( c ) ln( a ) dx av dx dx dx

du d n d u 1 du 1 dv d 1 1 du 1 dv d u log a cx n = cot n ( u ) = n csc 2 ( u ) cot ( n 1) ( u ) ln = log c = dx x ln a dx v u dx v dx dx dx v ln c u dx v dx dx d n d cot n ( u ) = n sec 2 ( u ) cot ( n +1) ( u ) du c n du d c u a v = c u a v ln( a ) dv + ln( c ) du d log a x n = c u = ln( c ) dx x ln a dx dx dx dxdx 2 u dx dx dy dy du dv = dx du dv dx
d x 1 x du d u 1 1 du 1 dv = dx u u 2 u 3 dx dx ln v = 2 u dx v dx

d du cot n ( u ) = n cot n ( u ) sec ( u) csc ( u ) dx dx d du sec n ( u ) = n sec n ( u ) tan( u ) dx dx d du csc n ( u ) = n csc n ( u) cot ( u) dx dx
d u ln m dx v
n

## 1 du d c n c d ln( x ) = 1 (1 ln( x ) ) d log ( ln u ) = c = dx u( ln c )( ln c ) dx n n +1 dx x dx xn x x

d c ln dx xn

n =x

d x 1 1 x = dx v v 2 x v

dv du dv dv u = vu v 1 + u v ln( u) dx dx dx dx

d u = dx v

d x du du dv d 1 1 du 1 u x ln ( u ) = + ln x u log c = dx u dx dx dx dx x ln c u dx x v2
nm u n m du = cm dx

n 1 du 1 dv m u dx v dx

## m u d du u du n d u n u ln( c ) = ln( c ) d c = c ln( c ) dx dx dx dx x n x n dx x c

n d ln x = 1 n m ln x n m m +1 dx x x

## 1 du d 1 1 du 1 dv d uv ln( log c u ) = log a = + u ln u dx dx c ln a u dx v dx dx

u v d 1 1 du 1 dv log a = + dx c ln a u dx 2v dx

1 du d u du d u du d u dv Log a u = c = c u ln( c ) = dx u ln a dx ( ) dx dx dx ln v dx v ln v dx

u d 1 1 du n log c = n dx x ln c u dx x